REFLEKSI AKSIOLOGIS ATAS TEORI BAHASA NOAM CHOMSKY DAN M.A.K HALLIDAY - Kurnianta, Paulus; Maharani, Septiana Dwiputri (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2020)
(Title: Axiological Reflections on Noam Chomsky's and M.A.K Halliday'sLanguage Theories). This article is meant to philosophically reflect Chomsky's and Halliday's language theories by focusing on the axiological dimension of their theoretical constructs, that is, what are the hidden values therein. To draw basic sketches of their theoretical constructs, their ontological and epistemological assumption are explored. Furthermore, Gruenberg's axiological scheme is adopted to discuss them. From the chains of reflection, it is found that in Chomsky's the positive pole of humanlanguage relation exists in language with internal, mental, logical-objective, formal, neutral, innate, certain, transparent, stable, alogarithmic and closed or un-contextual characteristics. The superior language is scientific, positivistic and logical language. Meanwhile, in Halliday's the positive pole exists in language with practical, external, semiotical, social, cultural, participatory, concrete, critical, dynamic, discursive, authentic, interpretative and open or contextual. The superior language is authentic language which is rich of signification.Key words: axiology, language theory, Chomsky, Halliday